Impact of margin distance on recurrence and survival following breast-conserving surgery after neoadjuvant systemic therapy - C. Florin Pop; Clémence Ortega; Mathilde Lecomte; Paulus Kristanto; Chirine Khaled; Filip De Neubourg; Antoine Desmet; Evandro De Azambuja; Denis Larsimont; Isabelle Veys (npj Breast Cancer)
Abstract Current evidence does not support the application of “no-ink-on-tumor” negative margins following breast-conserving surgery (BCS) in breast cancer (BC) patients who have received neoadjuvant systemic treatment (NST). We compared loco-regional free survival (LRFS), disease-free survival (DFS), and overall survival (OS) based on different tumor margin distance thresholds in a cohort of 235 BC patients treated with NST and subsequent BCS between 01/2015 and 12/2019. The 5-year LRFS was 81.6% in patients with “no-ink-on-tumour”, margins and 71.0% in those with positive margins (p = 0.584). Margins >1 mm were associated with superior outcomes, with a 5-year LRFS of 84.0% compared to 69.3% in patients with margins ≤1 mm (p = 0.005). Additionally, margins >1 mm were significantly correlated with longer DFS (p = 0.028) and OS (p = 0.001). These findings suggest that a surgical margin distance >1 mm provides the best LRFS, DFS, and OS outcomes for this group of BC patients.